Analysis and Design of a Magnetically Integrated Planar Transformer Adapted to CLLLC Converter - Zhao, Yifan; Liu, Boyu; Zhang, Xiangjun; Guan, Yueshi; Wang, Yijie; Xu, Dianguo (IEEE International Conference on Industrial Technology (Online), 2025)
In the future, high power density and planarization will still be the development directions of power electronic converters. The key to increasing power density lies in magnetic components. As an excellent bidirectional converter, the CLLLC resonant converter has three magnetic elements, making it difficult to improve its power density. This paper introduces a planar transformer with asymmetrically distributed windings. By adjusting the winding distribution, a controllable leakage inductance is obtained, which replaces the original resonant inductance and significantly reduces the volume of the converter. Moreover, the PCB winding method adopted in this paper reduces the number of layers of the original PCB board by half, greatly cutting the cost. A 500W prototype is built to verify the proposed magnetically integrated transformer.